Stimulating positive English speaking class environment - Ani Purjayanti (Jurnal Linguistik Terapan, 2012)
Despite the fact that the skills to communicate in English are crucial in the globalization era, the majority of students in Bogor Agricultural University encounter problems to speak this language appropriately and fluently. When asked to elaborate the inhibiting factors, students generally point out both linguistic and nonlinguistic factors. Accordingly, not only do students need to be equipped with adequate knowledge of grammar, a sufficient range of vocabulary, and pronunciation knowledge but their confidence and willingness to take the risk also need to be provoked as well. In fact, the latter points, namely, building confidence and risk-taking willingness generally require hard efforts on the part of the teachers. Practice, is indeed viewed as the best way in such an English teaching-learning process, although, inevitably, there are often questions concerning the how this process is able to provide prominent and meaningful inputs to the students. This paper is written as an attempt to elicit students’ opinions on speaking classroom environment which can stimulate and foster students to speak appropriately and fluently. 100 students of Bogor Agricultural University (of Diploma level) who had taken reading class prior to the Speaking I, were randomly selected to be the subjects of the study. Besides completing questionnaires focusing on classroom arrangement and environment, participants were interviewed for further clarification. Results show that teachers play the most prominent role in creating classroom environment, including creating comforting but challenging classroom environment and providing appropriate teaching materials.